Youth Mentoring To Build Ecological Awareness In Islamic Boarding Schools - Edo Dwi Cahyo; Hifni Septina Carolina; Suhendri, Resi; Khodijah; Yayuk Hidayah; Haikal; Suhono, Suhono (International Journal of Community Engagement Payungi, 2024)
Ecological awareness is increasingly recognized as a critical component of education, particularly in the context of Islamic boarding schools, which play a significant role in shaping the values and behaviors of young Muslims in Indonesia. The method used ABCD (Asset Based Community) to maximize the potential assets, which includes individual assets, communities, infrastructure, community, et al. The result showed that the mentoring activity at the Mambaul Huda Islamic boarding school was attended enthusiastically by dozens of male and female students and carried out according to schedule. Planting the value of ecological awareness should be done through daily habituation in the boarding school environment, as well as transformative education that solves environmental problems. One of the key benefits of mentorship in this context is the opportunity for experiential learning. Mentors can facilitate hands-on activities, such as tree planting, waste management projects, and community clean-up initiatives, which not only educate students about ecological principles but also encourage them to take an active role in their communities